Plan of attack - Woodward, Bob, 1943- (New York : Simon & Schuster, 2004)
Account of how and why President George W. Bush, his war council, and allies launched a preemptive attack to topple Saddam Hussein and occupy Iraq. Based on interviews with 75 key participants and more than three and a half hours of exclusive interviews with President Bush.
Includes index.
Includes bibliographical references and index.
Keywords: Iraq War, 2003- -- Causes; Bush, George W. -- 1946- -- Interviews; United States -- Officials and employees -- Interviews; United States -- Foreign relations -- 2001-; Politieke besluitvorming; Golfoorlog (2003); Militaire politiek; Terrorisme; Bestrijding; Al-Qaida.; Conflitos internacionais -- Estados unidos; z; Guerra -- Estados unidos; iraque